Sensibilidad de especies de hongos fitopatogenos a los inhibidores de la biosintesis de ergosterol (IBE) - Muiño, B.L.=700 1 Hernandez, A.; Porras, A.
(Es, En)
Ilus., 13 ref.
Keywords: GIBBERELLA FUJIKUROI; CHALARA PARADOXA; MYCOSPHAERELLA MUSICOLA; FUNGICIDAS; FUNGICIDAS; RESISTENCIA A LOS PLAGUICIDAS; CUBA